A simple widening technique of postlaryngectomy tracheostomal stenosis: Anchoring to the medial clavicle. (March 2023) - Roh, Jong-Lyel
Abstract: Tracheostomal stenosis is a common distressing problem for surgeons and patients after laryngectomy. The stenosis occurs in up to 44% of laryngectomized patients, according to different contributing factors. Various surgical techniques have been introduced to treat tracheostomal stenosis, showing no clear advantages over the other methods. Only a few studies have reported stomal widening techniques with the preservation of tracheoesophageal puncture (TEP). Tracheostomal restenosis may occur after the stomaplasty, often requiring revision surgery. A new surgical method was developed to preserve TEP and avoid stomal restenosis, including the bilateral vertical incisions of tracheostoma stenosis and anchoring to the clavicle. This operative technique is relatively safe, simple, less invasive and time-consuming, and preserves the TEP and voice prosthesis. Therefore, this article presents the surgical procedure, potential indications, and pros and cons of the new widening method of tracheostomal stenosis.